2008
DOI: 10.1111/j.1651-2227.2008.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high‐frequency ventilation for premature infants

Abstract: Nasal HFV is effective in decreasing pCO(2) in stable premature infants requiring nasal CPAP support. Long-term use of nasal HFV requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 18 publications
6
76
2
Order By: Relevance
“…It has all the benefits of NIPPV with the added advantage of not being as dependent on breath synchronization, something that can presently be difficult to achieve with NIPPV [9]. Limited studies on the clinical use of nHFO in neonates are available, [11,12,13] and the existing data do not adequately address CO 2 elimination efficacy. All available clinical studies of nHFO have reported on blood PCO 2 comparative changes pre and post initiation of this treatment modality [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has all the benefits of NIPPV with the added advantage of not being as dependent on breath synchronization, something that can presently be difficult to achieve with NIPPV [9]. Limited studies on the clinical use of nHFO in neonates are available, [11,12,13] and the existing data do not adequately address CO 2 elimination efficacy. All available clinical studies of nHFO have reported on blood PCO 2 comparative changes pre and post initiation of this treatment modality [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Its use also does not require synchronization of breaths as the patient can comfortably continue normal tidal breathing while on the ventilator and thus has the potential to provide superior noninvasive ventilation. Only a limited number of clinical studies have explored the use of noninvasive high-frequency ventilation but whether this strategy is able to support adequate gas exchange in neonates has not been thoroughly addressed [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Short-term observational studies have suggested initial mean airway pressure set to equal the previous CPAP, frequency set at 10 Hz, amplitude adjusted to obtain visible chest-wall vibration and increased every 30 min by 4 -6 units, if necessary, to maintain clinically appropriate chest-wall vibration, transcutaneous CO 2 , or blood gas values. 80,81 Clinical responses to HFV in preterm neonates in 2 small studies have been reported. Van der Hoeven et al 79 placed 21 preterm and term infants with moderate respiratory insufficiency on nasal HFV following CPAP.…”
Section: Nasal High-frequency Ventilationmentioning
confidence: 99%
“…72 A small interventional study in 14 very low birth weight infants on nCPAP revealed similar benefits when PCO 2 was measured before and after 2 hours of nHFOV. 73 Other observational studies revealed successful use of nHFOV as rescue therapy for nCPAP failure 74 and in the postextubation period. 75 To explore the future role that nHFOV could play in the treatment of RDS, further research on effectiveness and safety is needed.…”
mentioning
confidence: 99%